Large increases in public R&D investment are needed to avoid declines of US agricultural productivity - Ariel Ortiz-Bobea; Robert G. Chambers; Yurou He; David B. Lobell (Proceedings of the National Academy of Sciences, 2025)
Increasing agricultural productivity is a gradual process with significant time lags between research and development (R&D) investment and the resulting gains. We estimate the response of US agricultural Total Factor Productivity to both R&D investment and weather and quantify the public R&D spending required to offset the emerging impacts of climate change. We find that offsetting the climate-induced productivity slowdown by 2050 will require R&D spending over 2021 to 2050 to grow at 5.2 to 7.8% per year under a fixed spending growth scenario or by an additional $2.2 to $3.8B per year under a fixed supplement spending scenario (in addition to the current spending of ~$5B per year). This amounts to an additional $208 to $434B or $65 to $113B over the period, respectively, and would be comparable in ambition to the public R&D spending growth that followed the two World Wars.